Longitudinal Associations Between Core Self-Evaluation, Vital Exhaustion and Hair Cortisol in Teachers and the Mediating Effects of Resignation Tendency - Schneider, Sandra; Wettstein, Alexander; Tschacher, Wolfgang; Torchetti, Loredana; Jenni, Gabriel; Kühne, Fabienne; grosse Holtforth, Martin; La Marca, Roberto (Frontiers in Psychology, 2022)
This longitudinal study investigates the relationship between core self-evaluation and chronic psychobiological stress in 42 teachers. Self-report questionnaires were used to assess core self-evaluation, vital exhaustion, and resignation tendency. The concentration of cortisol was assessed using hair samples. One year after the initial measurement, vital exhaustion and hair cortisol were assessed again. Path-analytic mediational models showed that core self-evaluation strongly predicted vital exhaustion, and resignation tendency partially mediated this relationship. However, core self-evaluation did not predict hair cortisol concentration. These findings suggest that core self-evaluation plays a crucial role in predicting and preventing vital exhaustion.